Usage of Ti-TiO2 electrode in microbial fuel cell to enhance the electricity generation and its biocompatibility - Taskan, Ergin; Hasar, Halil; Ozkaya, Bestamin (My University, 2013)
Microbial fuel cell (MFC) provides the generation of electricity as bacteria on anode electrode oxidize organic content present in wastewater. This study presents simultaneously the electricity generation from two different synthetic wastewater mixtures using a new electrode in both anode and cathode compartments. Results showed that power output increased excessively in the case of Ti-TiO2 electrode. MFC reactors were mainly dominated by Geobacter, Shewanella, Pseudomonas and Clostridium species. The molecular results also demonstrated that Ti-TiO2 electrode is biocompatibility and able to be used in MFC because these species are electricity producing bacteria. © (2013) Trans Tech Publications, Switzerland.
2nd International Symposium on Manufacturing Systems Engineering, ISMSE 2013 -- 27 July 2013 through 29 July 2013 -- 100433
Keywords: Bioelectricity production; MFC; Synthetic wastewater; Ti-TiO2 electrode